PENGGUNAAN JERUK NIPIS (Citrus aurantifolia) DAN STRAWBERRY (Fragraria sp) SEBAGAI PENGAWET ALAMI TERHADAP DAYA SIMPAN BOLU GULUNG JAGUNG - Nurbaya, Nurbaya; Syam, Husain; Sukainah, Andi (Universitas Negeri Makassar, 2018)
The purpose of this research is to know the effect of the use of lime (Citrus aurantifolia) and strawberry (Fragraria sp) as natural preservative to the shelf life of roll cake and to know the level of panelist acceptance of roll cake. This research uses a complete randomized design of factorial pattern consisting of two factors namely: the first factor: type of natural preservative that are P1: strawberry, P2:Â lime and the second factor was a natural preservative concentration 0%, 2% and 4%. The results of organoleptic of test showed the most favored roll cake from panelist is corn flour substitution 50% and wheat flour 50%. Based on Proximate test results obtained the best treatment that is: water content of 34.07% in 4% lime treatment, ash content of 1.37% on control treatment, 0.44% fiber content on 4% strawberry treatment, 6.81% protein content on 2% strawberry , 52.59% carbohydrate content on 2% strawberry treatment. Research results have shown that shelf life of roll cake with the addition of lime 2% only last until day 6.